Power Transformations in Time-Series Models of Quarterly Earnings per Share. - Hopwood, W. S.; McKeown, J. C.; Newbold, P. (The Accounting Review, 1981)
Abstract ABSTRACT: For many quarterly time series of corporate earnings per share, the data indicate the desirability of incorporating a power transformation into the time series model. Our empirical results suggest that, for such series, this will generally lead to forecasts of improved quality. The resulting forecasts compare more favorably with those of financial analysts than do forecasts derived from models without the transformation parameter.